Preparation of sulfur vacancy modified NiCo2S4@NiCoS2 core-shell electrode material and its application in asymmetric supercapacitors. (20th June 2023) - Chen, Xudong; Wu, Yuan; Zhou, Yang; Xu, Zhenming; Wu, Cunqi; Li, Lei; Li, Cheng; Zhang, Xiaogang; Tong, Hao
Highlights: The synergistic effect exists in Vs -NiCo2 S4 @NiCoS2 core-shell electrode materials with interfacial sulfur vacancy modification. The Vs -NiCo2 S4 @NiCoS2 provides a capacitance of 3200 f g −1 with the 1 + 1>2 effect compared to Vs -NiCo2 S4 and NiCoS2 . The Vs -NiCo2 S4 @NiCoS2 @AC devices deliver up to 46.3 Wh kg −1 energy density at 799.8 W kg −1 power density. Abstract: Nickel-cobalt based bimetallic sulfide has attracted much attention as positive electrode materials for supercapacitors due to its microstructure designability. However, charge storage occurs mostly on the surface of the material, which limits the full utilization of the active material inside. Here, rich sulfur vacancies modified NiCo2 S4 @NiCoS2 (Vs -NiCo2 S4 @NiCoS2 ) core-shell structures are grown tightly on a nickel foam substrate and prepared as positive material for supercapacitors. The rich sulfur vacancies in the Vs -NiCo2 S4 "core" increase the electrochemical active sites and electron transport rates, while the amorphous NiCoS2 "shell" facilitates the rapid diffusion of ions. The results show that Vs -NiCo2 S4 @NiCoS2 core-shell structure has a specific capacitance of 3200 F g −1, achieving the effect of "1 + 1>2". The excellent electrochemical performance is attributed to the surface/interface modification of rich sulfur vacancies and the synergistic effect induced by heterogeneous core-shell boundaries. Moreover, the asymmetric supercapacitor Vs -NiCo2 S4 @NiCoS2 //AC exhibits an energy density of 46.3 Wh kg −1 and a power density of 799.8 W kg −1, as well as excellent cyclic stability (nearly 80% capacity retention after 10, 000 cycles). This work provides a new idea and strategy for core-shell structure design of nickel-cobalt sulfide electrode materials combined with surface/interface modification. Graphical abstract: Sulfur vacancy modified Vs -NiCo2 S4 @NiCoS2 core-shell structure electrode material has been synthesized by hydrothermal, chemical reduction and electrochemical deposition. Image, graphical abstract